Ceftazidime/Avibactam: Who Says You Can't Teach an Old Drug New Tricks? - Katie E. Barber; Jessica K. Ortwine; Ronda L Akins (Frontiers Media S.A., 2016)
Purpose: Gram-negative resistance continues to rise with treatment options becoming more limited. Ceftazidime/avibactam was recently approved in the United States and Europe, which combines an established third-generation cephalosporin with a new, unique, non-β-lactam β-lactamase inhibitor. This review conducts a thorough examination of structure, pharmacology, spectrum of activity, pharmacokinetics/pharmacodynamics, in vitro and clinical efficacy and safety/tolerability of ceftazidime/avibactam, as well as detailed future directions for the agent. Methods: Pubmed and clinicaltrials.gov searches, as well as abstracts from the 2015 Interscience Conference on Antimicrobial Agents and Chemotherapy/International Society of Chemotherapy (ICAAC/ICC) and ID Week meetings and the 2016 American Society of Microbiology Microbe meeting, were conducted from January 2004 - September 2016. Relevant search terms included ceftazidime, ceftazidime/avibactam, avibactam, NXL104 and AVE1330A. The US package insert for ceftazidime/avibactam (02/2015) and European public assessment report (06/2016) were also reviewed. Results: In vitro susceptibility for ceftazidime/avibactam displayed potent activity against many Enterobacteriaceae including extended-spectrum-β-lactamase (ESBL) and carbapenemase-producing strains, as well as Pseudomonas aeruginosa. Phase II clinical trials utilized for approval demonstrated comparable safety and efficacy to imipenem/cilistatin for treatment of complicated urinary tract infections (70.4% vs. 71.4%) and combined with metronidazole compared to meropenem in complicated intra-abdominal infections (91.2% vs 93.4%). Phase III data displayed non-inferior efficacy of ceftazidime/avibactam compared to doripenem for complicated urinary tract infections (70.2% vs 66.2%) and combined with metronidazole compared to meropenem in complicated intra-abdominal infections (82.5% vs 84.9%), as well as comparable safety. Ceftazidime/avibactam was well-tolerated but does require renal adjustments. Additionally, 3 case series and a single case report have demonstrated the potential for ceftazidime/avibactam against multidrug resistant organisms for compassionate use or failure after previous therapy. Conclusion: By adding avibactam to ceftazidime, clinicians' antimicrobial armamentarium is expanded, potentially increasing the ability to combat multi-drug resistant gram-negative pathogens, particularly ESBL and carbapenemase-producing organisms, as well as Pseudomonas aeruginosa.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.